2021
DOI: 10.1177/1756284821994736
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome and Clostridioides difficile infection: a closer look at the microscopic interface

Abstract: The pathogenesis of Clostridioides difficile infection (CDI) was recognized with its link to the use of antimicrobials. Antimicrobials significantly alter gut microbiota structure and composition, which led to the discovery of the association of this gut perturbation with the development of CDI. A number of factors implicated in its pathogenesis, such as advancing age, proton-pump inhibitors, and gastrointestinal diseases, are linked to gut microbiota perturbations. In an effort to better understand CDI, a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 63 publications
1
36
0
4
Order By: Relevance
“…With respect to potential respiratory pathogenic genera ( Haemophilus and Streptococcus) , there were no significant reduction in transcripts observed after application of cleanSURFACES ® intervention ( Figure 7 ) ( LaRocque and Ryan, 2019 ). Transcripts for the fecal biomarker taxa, Faecalibacterium , were significantly (P = 0.03) depleted on OBT surfaces ( Sehgal and Khanna, 2021 ). While observed reductions from Baseline to Post-intervention are not statistically significant for Enterococcus and Clostridioides , transcripts were shown to be depleted on OBT surfaces ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…With respect to potential respiratory pathogenic genera ( Haemophilus and Streptococcus) , there were no significant reduction in transcripts observed after application of cleanSURFACES ® intervention ( Figure 7 ) ( LaRocque and Ryan, 2019 ). Transcripts for the fecal biomarker taxa, Faecalibacterium , were significantly (P = 0.03) depleted on OBT surfaces ( Sehgal and Khanna, 2021 ). While observed reductions from Baseline to Post-intervention are not statistically significant for Enterococcus and Clostridioides , transcripts were shown to be depleted on OBT surfaces ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gut microbiota perturbations can be a precondition as well as a consequence of both IBD and CDI ( Missaghi et al, 2014 ; Guan, 2019 ; Sehgal and Khanna, 2021 ; Qiu et al, 2022 ). While co-occurrence of IBD and CDI is common ( Khanna et al, 2017 ), this study demonstrated that these two medical conditions also share common gut community signatures.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown a reduction in gut microbiota richness in patients with CDI compared to healthy controls, and in the first CDI episode compared to recurrent CDI ( Theriot et al 2011 ; 2014 ; Buffie et al 2015 ). Lack of bacteria with 7α-dehydroxylation activity leads to decreased secondary BA production ( Sehgal and Khanna 2021 ). It results in a a cause-and-effect relationship in which dysbiosis and BA pool alterations intensify and aggravate each other, leading inexorably to worsening of the situation, which could be described as a “vicious circle”.…”
Section: Bile Acid Pool Composition and Clostridioides Diff...mentioning
confidence: 99%